PERFORMANCE OF A CLOSED CYCLE POWER TAKE OFF FOR MUTRIKU BREAKWATER - Meskell, Craig (My University, 2022)
An oscillating water column (OWC) type wave energy converter was installed in Mutriku breakwater (Basque Country, Spain). The wave power is transferred to an air flow that turns a turbine. The facility currently uses self-rectifying turbines. A closed cycle power take off (CCPTO) arrangement, by forcing the flow to be unidirectional, would allow the use of more efficient turbines than currently employed. In this paper, a reduced order model for such a system is introduced. Using Mutriku breakwater dimensions the expected power performance is assessed. The sensitivity of the system to basic geometric features such as turbine and valves sizes is explored using monochromatic ideal wave. It is found that while there is an opimal size turbine, there is no benefit to increasing the valve size beyond a certain area. More realistic sea states representative of Mutriku are investi- gated using polychromatic waves as an input. The effect of tide is also considered by comparing extreme high and low tide conditions with the mean tide. It is found that tide height has a significant impact on the power production capacity. The trends uncovered by this work will form a useful basis for the design of the actual power take off including the unidirectional turbine
The 12th International Conference on Flow-Induced Vibration.
Keywords: Oscillating water column; Wave power; Renewable energy; Smart & Sustainable Planet